Whole genome sequencing of Clarireedia aff. paspali reveals potential pathogenesis factors in Clarireedia species, causal agents of dollar spot in turfgrass - Bahri, Bochra Amina; Parvathaneni, Rajiv Krishna; Spratling, Willis Turner; Saxena, Harshita; Sapkota, Suraj; Raymer, Paul L.; Martinez-Espinoza, Alfredo D. (Frontiers in Genetics, 2023)
Dollar spot is one of the most damaging diseases in turfgrass, reducing its quality and playability. Two species, Clarireedia monteithiana and C. jacksonii (formerly Sclerotinia homoeocarpa) have been reported so far in the US. To study the Clarireedia genome, two isolates H2 and H3, sampled from seashore paspalum in Hawaii in 2019 were sequenced via Illumina paired-end sequencing by synthesis technology and PacBio SMRT sequencing. Both isolates were identified as Clarireedia aff. paspali, a novel species in the US. Using short and long reads, C. aff. paspali H3 contained 193 contigs with 48.6 Mbp and presented the most completed assembly and annotation among Clarireedia species. Out of the 13,428 protein models from AUGUSTUS, 349 cytoplasmic effectors and 13 apoplastic effectors were identified by EffectorP. To further decipher Clarireedia pathogenicity, C. aff. paspali genomes (H2 and H3), as well as available C. jacksonii (LWC-10 and HRI11), C. monteithiana (DRR09 and RB-19) genomes were screened for fifty-four pathogenesis determinants, previously identified in S. sclerotiorum. Seventeen orthologs of pathogenicity genes have been identified in Clarireedia species involved in oxalic acid production (pac1, nox1), mitogen-activated protein kinase cascade (pka1, smk3, ste12), appressorium formation (caf1, pks13, ams2, rgb1, rhs1) and glycolytic pathway (gpd). Within these genes, 366 species-specific SNPs were recorded between Clarireedia species; twenty-eight were non-synonymous and non-conservative. The predicted protein structure of six of these genes showed superimposition of the models among Clarireedia spp. The genomic variations revealed here could potentially lead to differences in pathogenesis and other physiological functions among Clarireedia species.